Optimisation of Overload and Overcurrent Protection to Improving Operational Efficiency of Cone Crusher Motor - Kurniawan, Muhammad; Hasanah , Rini Nur; Nurwati, Tri; Soltana Guesmi (Faculty of Engineering, Universitas Brawijaya, 2025)
The mining industry occupies a pivotal position in the global economy, particularly in terms of supplying indispensable raw materials. A primary challenge confronting this industry is the imperative to preserve the reliability and operational efficiency of equipment, notably electric motors utilized in cone crusher machinery. The presence of overload and overcurrent issues in motors has the potential to induce operational disruptions, a decline in efficiency, and the prospect of irreversible damage. This research endeavors to optimize the overload and overcurrent protection system on the cone crusher motor to enhance operational efficiency at PT Amman Mineral Nusa Tenggara. The proposed methodology involves the utilization of MATLAB Simulink software, employing models of